Perlindungan Hukum Nasabah Pialang Perdagangan Berjangka Dalam Transaksi Valuta Asing Berdasarkan Pasal 50 Undang-Undang Nomor 10 Tahun 2011 Tentang Perubahan Atas Undang-Undang Nomor 32 Tahun 1997 Tentang Perdagangan Berjangka Komoditi - Frans Kurniyawan; Celina Tri Siwi K; Hermanto Silalahi (Universitas Katolik Widya Karya Malang, 2023)
Government effort to improve the citizen welfare requires a lot of funds, therefore the fund’s needed from investment at capital market is growing significantly. These needs spur the development of Indonesia’s commodity futures trading activities, foreign exchange trading included. Along with those development, rise a number of problems about fulfillment of customer’s legal protection. Fulfillment of such legal protection comes from two parties; first, from the state through Law No. 10 of 2011 and Bapebbti in form of Regulation of the Head of Bappebti, and from the futures trading broker as customer’s partner. The provisions governing the birth of customer and futures trading brokers relationship are regulated in Article 50 of Law No. 10 of 2011. Elements of law stated on it have provided legal protection that upholds the purposes of law such as justice, legal certainty, and benefits. Legal protection of the customer by futures trading broker is provided and can be measured by complying positive law